Case report: Exploring teduglutide as a therapeutic option for refractory microscopic colitis: insights and implications - Rim, Daniel Sungku; Shin, Jeong-Hun; Jacoba, Isa; Sharma, Kavita; Kim, Dong Wook (Frontiers in Medicine, 2023)
Microscopic colitis is a chronic inflammatory condition of the colon characterized by chronic watery diarrhea, generally with endoscopically normal or nonspecific findings, and can be diagnosed by histopathological examination of colon mucosal biopsies. Some patients experience severe symptoms that do not respond to conventional medical treatment. A glucagon-like peptide-2 (GLP-2) analog, teduglutide, is used in patients with short bowel syndrome (SBS) dependent on parenteral support. In this case report, we describe a patient with microscopic colitis who demonstrated significant symptom improvement following teduglutide treatment.